2011
DOI: 10.1371/journal.pone.0018226
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Ion-Channel Coupled Receptors as Conformational Motion Detectors

Abstract: Ion Channel-Coupled Receptors (ICCRs) are artificial proteins comprised of a G protein-coupled receptor and a fused ion channel, engineered to couple channel gating to ligand binding. These novel biological objects have potential use in drug screening and functional characterization, in addition to providing new tools in the synthetic biology repertoire as synthetic K+-selective ligand-gated channels. The ICCR concept was previously validated with fusion proteins between the K+ channel Kir6.2 and muscarinic M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 38 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…9,10 Additionally, artificial lipid membranes are increasingly utilized in a range of biomimetic chemical sensors, 1113 with much focus on-hemolysin nanopores for the detection and characterization of biopolymers and other biological analytes. 1421 The recent advent of engineered transmembrane proteins that combine the high sensitivity of ion channel conductance measurements with the specificity of molecular recognition, 22,23 presents a number of opportunities for novel sensor development. However, producing BLMs in a high density device format amenable to long-term monitoring applications, or to being integrated into robust and deployable analytical systems, presents a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Additionally, artificial lipid membranes are increasingly utilized in a range of biomimetic chemical sensors, 1113 with much focus on-hemolysin nanopores for the detection and characterization of biopolymers and other biological analytes. 1421 The recent advent of engineered transmembrane proteins that combine the high sensitivity of ion channel conductance measurements with the specificity of molecular recognition, 22,23 presents a number of opportunities for novel sensor development. However, producing BLMs in a high density device format amenable to long-term monitoring applications, or to being integrated into robust and deployable analytical systems, presents a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In ICCRs, the open probability of Kir6.2 is similar to that of the unfused channel (KΔ) and the channel is partly open at rest in our experimental conditions. This basal activity offers the advantage of sensing either agonist-evoked channel inhibition (shortened M2, rhodopsin and D2 L ICCRs) (Caro et al , 2012; Moreau et al , 2008) or activation (full-length M2, β2 ICCRs) (Caro et al , 2011; Moreau et al , 2008). In the case of the M2(T4L) ICCR, the physiological agonist acetylcholine (ACh) causes an inhibition of Kir6.2 comparable to that observed with the wt M2 ICCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to validate this concept with another GPCR, we used the previously created adrenergic β 2 -K ICCR (Caro et al , 2011) and inserted the T4L domain in the i3 loop. The position of the T4L domain was the same as in the first crystallized β 2 (T4L) receptor (Rosenbaum et al , 2007), but the glycosylation sites were left intact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of β 2 AR-Gs complex could provide some information about the essential mechanism of structural events linking GPCR-Gs protein complex formation by using peptide amide hydrogen-deuterium exchange mass spectrometry [13]. Engineering and characterization of β 2 AR-based on ion-channel coupled receptors gave new insights into the conformational dynamics of β 2 AR [14]. All these studies also indicated that it was difficult to obtain the crystal structure of the agonist-bound to active conformation of β 2 AR if the G protein did not bind to β 2 AR.…”
Section: Introductionmentioning
confidence: 99%